Left ventricular remodeling in aortic stenosis patients referred for surgical aortic valve replacement. (3rd October 2022) - R Santos, R; Abecasis, J; Maltes, S; Mendes, G S; Oliveira, L; Horta, E; Guerreiro, S; Freitas, P; Ferreira, A; Ribeiras, R; Andrade, M J; Cardim, N; et al.
Abstract: Background: Left ventricular (LV) hypertrophy is a common expected finding in aortic stenosis (AS) patients. Cardiac magnetic resonance (CMR) plays an important role as a non-invasive method for determining LV mass and volume, and to characterize the LV remodeling response in AS. Aim: To assess the prevalence, to describe the patterns and evolution of LV remodeling (by CMR) in AS patients referred for surgical aortic valve replacement (AVR). Methods: Single-center prospective cohort of 132 consecutive patients (73 years [68–77 years], 49% men] with severe AS: mean transaortic pressure gradient (AVmean): 61±1.5 mmHg; aortic valve area (AVA): 0.7±0.1 cm 2, referred for surgical AVR, with no previous history of ischemic cardiomyopathy. Before surgery, all patients underwent electrocardiogram, complete transthoracic echocardiogram (TTE) and CMR for LV assessment and tissue characterization (mean LV indexed mass [LVMi]: 80.3±26.5 g/m 2 ; mean end-diastolic LV indexed volume [LVEDVi]: 84.4±24.5 mL/m 2 and median geometric remodeling ratio [M/V]: 0.95 g/mL [IQR 0. 81–1.08 g/mL]). Patterns of LV remodeling were investigated before and after AVR by CMR measurements of LVMi, LVEDVi and M/V. Besides normal LV ventricular structure, four other patterns were considered: concentric remodeling, concentric hypertrophy, eccentric hypertrophy, and adverse remodeling (Figure 1). Results: Overall, 43% (n=58) of the patients had concentric hypertrophy, 30% (n=40) concentric remodeling, 22% (n=29) normal ventricular geometry, 4% (n=5) eccentric hypertrophy and in two patients we observed an adverse remodeling pattern. AVR was performed in 80 patients. At the 3rd to 6th month post-AVR assessment, LV remodeling changed to: normal ventricular geometry in 46%, concentric remodeling in 31%, concentric hypertrophy in 19%, eccentric hypertrophy in 3% and adverse remodeling in only one patient (Figure 1). Conclusions: In this group of patients with severe aortic stenosis, concentric hypertrophy was not the sole pattern of LV remodeling and two out of every five still presented a normal ventricular geometry and mass as assessed by CMR. LV response was dynamic after AVR which stands for complex and multifactorial interaction in these group of patients despite similar valvular pathophysiology and therapeutic intervention. Funding Acknowledgement: Type of funding sources: None.